A Case Study of iPad Implementation in One Rural Elementary School. (December 2019) - Corey, Lesley
The study explored the implementation of a 1:1 iPad initiative with a focus on leadership. The distributed leadership model provided the framework using semistructured interviews as the primary source of data collection. Using the distributed leadership model, the researcher examined the role of school leaders. Four emerging themes were identified: time, access, technical support, and professional development. Results showed that successful implementation of a 1:1 iPad program requires advanced planning including time to obtain new skills and to research and explore the vast potential of the iPad in an environment where technical assistance is available within reasonable time constraints.